630 Trends in prevalence of drink driving and speeding in two chinese two cities from 2010 to 2014: evaluating a five-year project. (1st September 2016) - Li, Qingfeng; He, Huan; Duan, Leilei; Wang, Yuan; Bishai, David M; Hyder, Adnan A
Abstract : Background: Road traffic injuries are a serious public health challenge and impose huge health and economic burden in China. To address the problem, Bloomberg Philanthropies funded a consortium of international partners to design and implement targeted interventions, such as social media campaigns, advocacy for legislative change, and law enforcement training, to reduce the percentage of drink driving and speeding in two Chinese cities from 2010 to 2014. This is one of few road safety projects in China that involve multiple international partners and domestic stakeholders. Methods: To monitor and evaluate the project, observational data on speeding were regularly collected from representative samples in both Chinese cities. Data on drinking and driving were collected in collaboration with local traffic police using breathalysers. Results: The analysis based on 15 rounds of data show that from May 2011 to Nov 2014, the percentage of vehicles driving above speed limit decreased from 31.77% (95% CI: 29.16–34.47) to 7.40% (95% CI: 6.96–7.85) in Dalian and from 13.50% (95% CI: 11.69–15.47) to 6.86% (95% CI: 6.39–7.36) in Suzhou. Drink driving decreased from 1.64% (95% CI: 1.10–2.36) in Jan 2011 to 0.50% (95% CI: 0.24–0.92) in Nov 2014 in Dalian and from 5.66% (95% CI: 4.75–6.69) to 0.33% (95% CI: 0.04–1.20) in Suzhou during approximately the same period. All changes are statistically significant. Conclusions: Despite the difficulty in attributing the changes to the program due to the lack of control cities, the substantial reduction in the prevalence of the two risk factors suggests that through coordinated actions, internationally recognised best practices in road safety are effective in improving Chinese road traffic safety.